Effects of different post-activation potentiation warm-ups on repeated sprint ability in soccer players from different competitive levels - Sanchez-Sanchez, J.; Rodriguez, A.; Petisco, C.; Ramirez-Campillo, R.; Martinez, C.; Nakamura, F. Y. (Journal of Human Kinetics, 2018)
This study aimed to compare the effects of a traditional warm-up with two post-activation potentiation (PAP) warm-up strategies on the repeated sprint ability (RSA) of soccer players from national (NL) and regional (RL) competitive levels. Sixteen young players (NL, n = 8, age = 20.7 ± 1.4 y, body mass = 68.5 ± 7.0 kg, body height = 177.4 ± 5.2 cm; RL, n = 8, age = 20.8 ± 1.0 y, body mass = 68.7 ± 4.0 kg, body height = 176.6 ± 5.6 cm) were recruited to complete a traditional warm-up (CONTROL), a PAP warm-up incorporating squats with a load (~60% 1RM) that allowed a high speed (1 m/s) of movement and a high number of repetitions (PAP-1), and a PAP warm-up with a load (~90% 1RM) that allowed a moderate speed (0.5 m/s) of movement and a reduced number of repetitions (PAP-0.5). A RSA test (six 20-m sprints with 20 s of recovery) was performed 5 min after the PAP warm-up to assess the effects of the different protocols on the fastest sprint (RSAb) and the mean time of all sprints (RSAm). A meaningful improvement of RSA performance was observed with PAP-0.5, attaining a large effect on NL (RSAb, ES = -1.5; RSAm, ES = -1.3) and only a small effect on RL athletes (RSAb and RSAm, ES = -0.2). Moreover, when each RSA sprint performance was compared between NL and RL players, after PAP-0.5 greater performance for all sprints was observed in the NL players. Therefore, adding a heavy strength-based conditioning exercise during the warm-up prior to a RSA test may induce significant performance improvements in NL, but only small effects in RL players.